Local residents’ perception on socio-economic impact of Iskandar Malaysia - Mohamed Osman, Mariana; Bachok, Syahriah; Rabe, Noor Suzilawati (Elsevier, 2014)
One of the urban regeneration programme to promote for urbanization and economic growth in Malaysia is through the implementation of regional economic development policies and strategies. This paper discusses the strength and potential of Iskandar Malaysia development from the regional development perspectives, Iskandar Malaysia contribution towards the socio-economic development and analyse the local people’s perceived socio-economic impacts of Iskandar Malaysia development. Review on secondary and data collection on primary data were done to achieve objectives in the study. The study found that more cooperation and attention from the local authorities, stakeholders and public is needed to ensure urban regeneration through programme can be successfully implemented in Malaysia.